2023
DOI: 10.1007/s11547-023-01613-w
|View full text |Cite
|
Sign up to set email alerts
|

The added value of the visual analysis of DWI in post-surgery follow-up of soft tissue sarcoma of the extremities: do we really need ADC?

Abstract: Introduction MRI has a fundamental role in the follow-up of soft tissue sarcomas (STSs). However, the differentiation of recurrences/residual disease from post-surgical changes is a complex task, with a central role for the radiologist. Materials and methods We retrospectively evaluated 64 post-surgery MRI for extremities STSs. MR protocol included DWI (b = 0, 1000). Two radiologists were asked to consensually evaluate: presence/absence of tumoral nodules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Using ADC values, the noticeable therapeutic efficacy of Gd@HbCe6-PEG nanoparticles was quantitatively confirmed at 6 h after PDT, much earlier than that (day 2 post-PDT) evaluated by structural MRI. Stroeder et al [29] showed that the patients with a good tumor response had higher ADC values than non-responders, confirming that DWI can be a useful method for more accurate assessment of tumor response and the ADC values can be used as prognostic markers. However, the DWI signal and ADC values are strongly influenced by the scan parameters, which have not been standardized, and the optimal scanning parameters are not uniform from site to site, leading to differences in results obtained in similar studies [30].…”
Section: Functional Mri For Anticancer Therapy Evaluationmentioning
confidence: 95%
“…Using ADC values, the noticeable therapeutic efficacy of Gd@HbCe6-PEG nanoparticles was quantitatively confirmed at 6 h after PDT, much earlier than that (day 2 post-PDT) evaluated by structural MRI. Stroeder et al [29] showed that the patients with a good tumor response had higher ADC values than non-responders, confirming that DWI can be a useful method for more accurate assessment of tumor response and the ADC values can be used as prognostic markers. However, the DWI signal and ADC values are strongly influenced by the scan parameters, which have not been standardized, and the optimal scanning parameters are not uniform from site to site, leading to differences in results obtained in similar studies [30].…”
Section: Functional Mri For Anticancer Therapy Evaluationmentioning
confidence: 95%